Lessons for Other Developing Countries from Recent Asian Financial Crisis - Jangkung Handoyo Mulyo (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 1999)
The Asian financial crisis was triggered by the speculative attack on the dpmestic currincies.